Rheumatic Heart Disease Treatment Cascade in Uganda. Issue 11 (November 2017) - Longenecker, Chris T.; Morris, Stephen R.; Aliku, Twalib O.; Beaton, Andrea; Costa, Marco A.; Kamya, Moses R.; Kityo, Cissy; Lwabi, Peter; Mirembe, Grace; Nampijja, Dorah; Rwebembera, Joselyn; Sable, Craig; et al.
Abstract : Background—: Rheumatic heart disease (RHD) is a leading cause of premature death and disability in low-income countries; however, few receive optimal benzathine penicillin G (BPG) therapy to prevent disease progression. We aimed to comprehensively describe the treatment cascade for RHD in Uganda to identify appropriate targets for intervention. Methods and Results—: Using data from the Uganda RHD Registry (n=1504), we identified the proportion of patients in the following care categories: (1) diagnosed and alive as of June 1, 2016; (2) retained in care; (3) appropriately prescribed BPG; and (4) optimally adherent to BPG (>80% of prescribed doses). We used logistic regression to investigate factors associated with retention and optimal adherence. Overall, median (interquartile range) age was 23 (15–38) years, 69% were women, and 82% had clinical RHD. Median follow-up time was 2.4 (0.9–4.0) years. Retention in care was the most significant barrier to achieving optimal BPG adherence with only 56.9% (95% confidence interval, 54.1%–59.7%) of living subjects having attended clinic in the prior 56 weeks. Among those retained in care, however, we observed high rates of BPG prescription (91.6%; 95% confidence interval, 89.1%–93.5%) and optimal adherence (91.4%; 95% confidence interval, 88.7–93.5). Younger age, latent disease status, and access to care at a regional center were the strongest independent predictors of retention and optimal adherence. Conclusions—: Our study suggests that improving retention in care—possibly by decentralizing RHD services—would have the greatest impact on uptake of antibiotic prophylaxis among patients with RHD in Uganda. Abstract : Supplemental Digital Content is available in the text.